Meta-analysis of silicosis and lung cancer - Lacasse, Yves; Martin, Sylvie; Simard, Serge; Desmeules, Marc (Scandinavian Journal of Work, Environment & Health, 2005)
' ' OBJECTIVES ': 'This study examined the association between silicosis and lung cancer in a systematic review (and meta-analysis) of the epidemiologic literature, with special reference to the methodological quality of observational studies. ' ' METHODS ': 'We searched Medline, Toxline, BIOSIS and Embase (1966–May 2004) for original articles published in any language and systematically reviewed the bibliographies of the retrieved articles. Observational studies (cohort and case–control studies) were selected if they reported a measure of association [standardized mortality ratio (SMR), relative risk or odds ratio] relating lung cancer to silicosis. ' ' RESULTS ': 'Thirty-one studies (27 cohort studies, 4 case–control studies) met the inclusion criteria of the meta-analysis. Without any adjustment for smoking, the meta-analysis of the cohort studies indicated that the common SMR was 2.45 [95% confidence interval (95% CI) 1.63–3.66; homogeneity P<0.0001]. By pooling the results of the cohorts for which mortality data were adjusted for smoking, the common SMR was 1.60 (95% CI 1.33–1.93; homogeneity P=0.52). In a “dose–response” analysis, the profusion of small and large opacities found in chest X-rays correlated with the risk of death from lung cancer. Overall, the case–control studies were more conservative in their conclusions. ' ' CONCLUSIONS ': 'Because of biases inherent to observational studies, it is likely that the risk of lung cancer among silicosis patients is overestimated in the current literature. There is nevertheless evidence, from data restricted to never smokers and from a “dose–response” analysis, that silicosis and lung cancer are associated.
Keywords: lung cancer; lung neoplasm; meta-analysis; pulmonary fibrosis; review; silica; silicosis; systematic review